Promoting Social Distancing during Covid-19 outbreak-An application of Health Belief Model in the context of Assam, India - Barman, Arpana; Deka, Moni (Journal of Advanced Research in Journalism & Mass Communication, 2019)
Social Distancing is one of the key preventive measures for reducing transmission of Covid-19 as recommended by WHO. During outbreaks of infectious disease, mass media plays a very critical role in Health Promotion and promoting healthy behaviour in the public for reducing transmission of the disease. Individual behaviour is dependent on the vulnerability of the individual towards the threat of the disease and there are modifying factors which affects the vulnerability. Decision making of individual behaviour change is very clearly explained by the Health Belief Model developed by Becker. The present qualitative study tries to understand the promotion of the concept of Social Distancing during the Covid-19 outbreak in Assam, India and tries to understand the individual behaviour change through the application of the Health Belief Model. As described by WHO, an outbreak of infectious disease needs special risk communication as outbreak communication and has a behavioural component into it. The concept of Social Distancing is a behavioural component for promotion of which behavioural change model like the Health Belief Model will help in developing the communication strategy for the promotion of long term Social Distancing behaviour through Mass Media. How to cite this article: Barman A, Deka M. Promoting Social Distancing during Covid-19 outbreak-An application of Health Belief Model in the context of Assam, India. J Adv Res Jrnl Mass Comm 2019; 6(4): 18-28 DOI: https://doi.org/10.24321/2395.3810.201909